(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores Kutadgu Bilig, a medieval philosophical and didactic work by Yusuf Khos Hajib, as a foundational text for spiritual and moral education. The study examines its ethical and pedagogical principles, highlighting its relevance in contemporary moral instruction. The work presents a framework for righteousness, justice, and wisdom, which are essential for shaping ethical individuals. By analyzing its historical context and philosophical underpinnings, this paper underscores its enduring significance in modern educational paradigms.